2020
DOI: 10.2147/copd.s233461
|View full text |Cite
|
Sign up to set email alerts
|

<p>Serum IL-8 and VEGFA are Two Promising Diagnostic Biomarkers of Asthma-COPD Overlap Syndrome</p>

Abstract: Background: Asthma-COPD overlap (ACO; previously referred to as asthma-COPD overlap syndrome) is characterized by persistent airflow limitation consistent with COPD, together with several distinguishing features of asthma. Asthma-COPD overlap syndrome is a condition of mixing symptoms of asthma and COPD, because of its complexity, it is difficult to find effective diagnostic markers in clinic. Purpose: Our aims were to detect the expression of serum cytokines in patients with asthma, explore the diagnostic pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 27 publications
0
24
0
2
Order By: Relevance
“…The serum levels of IL-9, vascular endothelial growth factor A (VEGFA) and placental growth factor (PIGF) in patients with ACO are significantly higher than in non-ACO asthmatics, while the levels of IL-8 and IL-17A are lower in ACO compared to asthmatics. 63 …”
Section: Biomarkers Of Acomentioning
confidence: 99%
See 1 more Smart Citation
“…The serum levels of IL-9, vascular endothelial growth factor A (VEGFA) and placental growth factor (PIGF) in patients with ACO are significantly higher than in non-ACO asthmatics, while the levels of IL-8 and IL-17A are lower in ACO compared to asthmatics. 63 …”
Section: Biomarkers Of Acomentioning
confidence: 99%
“…The serum levels of IL-9, vascular endothelial growth factor A (VEGFA) and placental growth factor (PIGF) in patients with ACO are significantly higher than in non-ACO asthmatics, while the levels of IL-8 and IL-17A are lower in ACO compared to asthmatics. 63 Recently, it was reported that 11 metabolites: serine, threonine, ethanolamine, glucose, cholesterol, 2-palmitoylglycerol, stearic acid, lactic acid, linoleic acid, D-mannose, and succinic acid, were found to be significantly altered in ACO as compared with asthma or COPD. 64 This provides novel insights into metabolic pathways and inflammatory mediators involved in the mechanisms underlying ACO and how these processes may be linked to each other and also with the pulmonary function impairment.…”
Section: Biomarkers Of Acomentioning
confidence: 99%
“…For example, Ding et al demonstrated that the serum VEGFA is one promising diagnostic biomarker of asthma-COPD overlap syndrome. 21 In addition, evidence suggested that SIRT1 and FOXO1 mRNA expression levels in PBMCs correlate to physical activity in COPD patients. 22 We intend to explore more potential autophagyrelated genes of COPD in the future.…”
mentioning
confidence: 99%
“…RANTES/CCL5 is also associated with airway inflammation and airway hyperresponsiveness, as we and others previously reported, 19,20 which is also supported by the present results. Interestingly, a high level of VEGF-A, which is correlated with decreased pulmonary function, 21 was also significantly more common in overweight patients with asthma, supporting the lower FVC and FEV1, compared to non-overweight asthma patients. There are two limitations in this study.…”
Section: Discussionmentioning
confidence: 72%